Uma nova estratégia de negociação em pares - Brito, Igor Arantes (2014)
One of the main advantages of pairs trading strategies is that it should normally entail low correlation with market returns. By taking both long and short positions, they are able to control the magnitude of the market beta, keeping it virtually close to zero. The idea is to carry out statistical arbitrage by taking advantage of deviations from long-run equilibrium prices. As such, they involve equilibrium correction models for a pair of asset returns. We show how to build a pairs trading strategy that benefits not only from the long-run equilibrium relation between the pair of asset prices, but also from the speed at which the prices correct deviations to that equilibrium. The vast majority of trading strategies involving pairs trading was based on the hypothesis that achieving positive returns would be related to the mean reversion characterized by the cointegration relation from each pair, but ignored the possibility of selecting pairs, testing the adjustment speed of the Vector Error Correction from this relationship. The overall result of this research indicates low correlation with market returns, associated with an net annual return and annualized Sharpe ratio of 15.05% and 1.96, respectively.